2010
DOI: 10.1089/lap.2009.0395
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical Multiple-Port Laparoscopic Cholecystectomy (TUMP-LC): A Prospective Analysis of 50 Initial Patients

Abstract: TUMP-LC is both feasible and safe. It can be performed with standard laparoscopic instruments, and, thus, there is minimal additional challenge to an experienced laparoscopic surgeon. With progressive experience and development in technology, TUMP-LC will probably be performed widely. But, disciplined, evidence-based investigations and randomized studies comparing it to existing techniques must be carried out before the actual place of this procedure in current surgical practice is determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…The ports and instruments for this approach were designed for use in adults, which has led to an extensive experience in this population [5][6][7][8]. In fact, randomized studies in adults suggest that outcomes in single-incision laparoscopic cholecystectomy are comparable with those found in the traditional multiport operation [9,10].…”
mentioning
confidence: 99%
“…The ports and instruments for this approach were designed for use in adults, which has led to an extensive experience in this population [5][6][7][8]. In fact, randomized studies in adults suggest that outcomes in single-incision laparoscopic cholecystectomy are comparable with those found in the traditional multiport operation [9,10].…”
mentioning
confidence: 99%
“…We have reported our learning curve in transumbilical multiple-port laparoscopic cholecystectomy and a trend towards reduced operative times with more experience [12]. We also reported that the difficulty of the procedure was due to confined operating space, in line positioning of laparoscope, close proximity of working instruments with limited triangulation, limited range of motion of laparoscope and instruments, and decreased number of ports.…”
Section: Discussionmentioning
confidence: 99%
“…LESS and NOTES are typical examples of such techniques. A considerable number of studies have been performed (1719) and advancements have been achieved. In our case, however, problems arose during the process of popularization mainly due to the disadvantages, including the use of specialized instrumentation and higher surgical costs.…”
Section: Discussionmentioning
confidence: 99%